Artificial urinary sphincter or a second adjustable transobturator male system offer equivalent outcomes in patients whom required revision on the initial ATOMS device: An international multi‐institutional experience. Issue 3 (1st March 2021) - Angulo, Javier C.; Schönburg, Sandra; Giammò, Alessandro; Queissert, Fabian; Gonsior, Andreas; González‐Enguita, Carmen; Martins, Francisco E.; Rourke, Keith; Cruz, Francisco
Abstract: Aim: To evaluate treatment options after surgical revision of adjustable transobturator male system (ATOMS) and the results of further incontinence implantation. Materials and Methods: A retrospective multicenter study evaluating patients with surgical revision of ATOMS in academic institutions. Causes and factors affecting revision‐free interval were studied and also the frequency of device explant and placement of second ATOMS or artificial urinary sphincter (AUS) at surgeon discretion. Operative results, complications (Clavien–Dindo), and efficacy (postoperative pad‐test, pad‐count, patient satisfaction, and patient global impression of improvement [PGI‐I scale]) of each treatment option were compared. Results: Seventy‐eight out of 902 patients (8.65%) with ATOMS underwent surgical revision at 4.1 ± 2.4 years mean follow‐up and 75 (8.3%) were explanted. The main causes for revision included persistence of incontinence (35.9%) and scrotal port erosion (34.6%). Independent risk factors of the shortened revision‐free interval were previous anti‐incontinence surgery (HR, 1.83; 95% CI, 1.06–3.16; p = 0.007) and port erosion (HR, 1.83; 95% CI, 1.06–3.16; p = 0.0027). Fifty‐eight (6.4%) received a second implant: 31 repeated ATOMS and 27 AUS. Operative time was longer for AUS ( p = .003). The visual analog scale of pain at hospital discharge ( p = 0.837) and postoperative complications ( p = 0.154) were equivalent. The predominant cuff size for AUS was 4.5 cm (59.3%). Mean follow‐up after the second implant was 29.1 ± 25.8 months. Postoperative efficacy of secondary treatment results favored ATOMS based on pad‐test ( p = 0.016), pad‐count ( p = 0.029), patient satisfaction ( p = 0.04), and PGI‐I ( p = 0.025). Conclusions: ATOMS surgical revision due to different reasons generally leads to device explant. Rescue treatment is possible with ATOMS or AUS. No difference in postoperative complications was detected between secondary devices, but efficacy favors repeating ATOMS implantation.